Estratégia de produção e competitividade :estudo de caso com enfoque de estratégia de foco em empresas de fibra de vidro - Ferreira, Evans Paiva da Costa (2006)
The objective of this thesis is to study the theory of production as it relates to and focuses on the strategy of production and competitiveness. The theory utilized was based on Terry Hill s Strategies through the utilization of Matrix of Manufacturing Strategy Issues and supported by the studies of others in this area. The methodology used for the development of this study was based on observing the engagement between two companies over a long period of time. Through interviews and discussions it was possible to collect the necessary information to guide this study; and by constant involvement in each of these companies, their ways of thinking, performing and administrating were observed and understood. In conclusion, this work created an understanding of the importance of the strategy of production, not as the only important element but as an important factor to direct attitudes and decisions in the company under the concept of strategy and competitiveness